The role of collective efficacy in long‐term condition management: A metasynthesis. (24th June 2019) - Vassilev, Ivaylo; Band, Rebecca; Kennedy, Anne; James, Elizabeth; Rogers, Anne
Abstract: Social networks have been found to have a valuable role in supporting the management of long‐term conditions. However, the focus on the quality and how well self‐management interventions work focus on individualised behavioural outcomes such as self‐efficacy and there is a need for understanding that focuses on the role of wider collective processes in self‐management support. Collective efficacy presents a potentially useful candidate concept in the development and understanding of self‐management support interventions. To date it has mainly been utilised in the context of organisations and neighbourhoods related to social phenomena such as community cohesion. Drawing on Bandura's original theorisation this meta‐synthesis explores how studies of collective efficacy might illuminate collective elements operating within the personal communities of people with long‐term conditions. A qualitative meta‐synthesis was undertaken. Studies published between 1998 and 2018 that examined collective efficacy in relation to health and well‐being using qualitative and mixed methods was eligible for inclusion. Timing of engagement with others, building trust in the group, and legitimising ongoing engagement with the group arised as central elements of collective efficacy. The two themes forming third order constructs were related to the presence of continuous interaction and ongoing relational work between members of the group. Collective efficacy can develop and be sustained over time in a range of situations where individuals may not have intense relationships with one another and have limited commitment and contact with one another. Extending this to the personal communities of people with long‐term conditions it may be the case that collective efficacy enables a number of engagement opportunities which can be oriented towards assisting with support from networks over a sustained length of time. This may include negotiating acceptable connections to resources and activities which in turn may help change existing practice in ways that improve long‐term condition management.